CAUSATIVE VARIABLES FOR DROP-OUT AND SUGGESTIONS FOR RETENTION OF STUDENTS IN HOME/ COMMUNITY SCIENCE - RAGINI RANAWAT*; SHATAKSHI SEMWAL (The Journal of Research ANGRAU, 2020)
The research (conducted under the ICAR funded extramural project) was carried out purposively with the college students and faculty staff selected from Home/Community Science colleges/departments from six universities across five states to find out the causative variables that have an impact on the enrolment percentage in Home/Community Science. The information was collected through an online Google form, from a total of 166 students and 51 faculty staff, respectively. According to the respondents, inactive placement cell (66.3% students & 56.9% faculty staff), lack of collaboration with the industries, institutions, and universities (48.2% students) and less dynamic practical classes linked to job providers (49.4% students & 49% faculty staff) were the major causes that lead to student drop-outs. Furthermore, the suggestions for retention of students pertained to holding open sessions on career opportunities and higher studies (65.7% students), regular orientations among students and industry representatives (57.8% students), and publicity of the subject through online media platforms (88.2% faculty staff) promotes effective and efficient working. It was clear from the study that there is a need to upgrade the operation of Home/Community Science education.